Future flavour physics experiments - Harnew, N (Wiley, 2015)
The current status of flavour physics and the prospects for present and future experiments will be reviewed. Measurements in B-physics, in which sensitive probes of new physics are the CKM angle γ, the Bs mixing phase ϕs, and the branching ratios of the rare decays B(s)0→μ+μ- , will be highlighted. Topics in charm and kaon physics, in which the measurements of ACP and the branching ratios of the rare decays K→πνν¯ are key measurements, will be discussed. Finally the complementarity of the future heavy flavour experiments, the LHCb upgrade and Belle-II, will be summarised.